DIABETES INSIPIDUS AS A CLINICAL SIGNS FOR ADULT LANGERHANS CELL HISTIOCYTOSIS: A CASE SERIES - S, Norainon Jariah; I, Shartiyah; N, Azraai Bahari; M, Masni; MN, Nurain; H, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Central diabetes insipidus (CDI) is characterized by polyuria, nocturia and polydipsia mainly by reduction of antidiuretic hormone secretion from the neurohypophyseal system. It is a rare condition. CDI more frequently caused by inflammatory processes and neoplastic infiltrations in adults as seen in germinoma, craniopharyngioma and Langerhans cell histiocytosis (LCH). Remote cases such as trauma resulting from surgery or by accident and genetic defects in the synthesis of vasopressin can also lead to CDI. Otherwise, about 30 to 50 per cent of cases is idiopathic. METHODOLOGY We reported three cases who are diagnosed to have Langerhans cell histiocytosis with CDI encountered by our endocrine department, Hospital Putrajaya. RESULTS Two women were diagnosed with CDI following the typical presentation of polyuria, polydipsia and extreme thirst. Biochemical evaluation consistent with hyperosmolar hypernatraemia followed by subsequent water deprivation test confirmed the diagnosis for both of them. Supplementation with MRI has shown both women also had a thickened pituitary stalk. Surprisingly, following that, cervical lymphadenopathy was seen in one woman and the other developed lytic lesion of the femur. Confirmatory diagnosis of LCH was made in both women following tissue biopsy of the respective area, thus they were co-managed by our haematology team. On the other hands, we have one man diagnosed with CDI following a year of LC diagnosis and currently on hormone replacement therapy. CONCLUSION Our cases concluded that CDI can precede the diagnosis of LCH or can happen following the diagnosis of LCH. Hence, the diagnosis of LCH should be considered in an adult who presented with CDI symptoms.